Intranasal Vaccination with Replication-Defective Adenovirus Type 5 Encoding Influenza Virus Hemagglutinin Elicits Protective Immunity to Homologous Challenge and Partial Protection to Heterologous Challenge in Pigs - Braucher, Douglas R; Henningson, Jamie N; Loving, Crystal L; Vincent, Amy L; Kim, Eun; Steitz, Julia; Gambotto, Andrea A; Kehrli, Marcus E (Clinical and Vaccine Immunology, 2012)
Influenza A virus (IAV) is widely circulating in the swine population and causes significant economic losses. To combat IAV infection, the swine industry utilizes adjuvanted whole inactivated virus (WIV) vaccines, using a prime-boost strategy. These vaccines can provide sterilizing immunity toward homologous virus but often have limited efficacy against a heterologous infection.There is a need for vaccine platforms that induce mucosal and cell-mediated immunity that is cross-reactive to heterologous viruses and can be produced in a short time frame. Nonreplicating adenovirus 5 vector (Ad5) vaccines are one option, as they can be produced rapidly and given intranasally to induce local immunity. Thus, we compared the immunogenicity and efficacy of a single intranasal dose of an Ad5-vectored hemagglutinin (Ad5-HA) vaccine to those of a traditional intramuscular administration of WIV vaccine. Ad5-HA vaccination induced a mucosal IgA response toward homologous IAV and primed an antigen-specific gamma interferon (IFN-gamma) response against both challenge viruses. The Ad5-HA vaccine provided protective immunity to homologous challenge and partial protection against heterologous challenge, unlike the WIV vaccine. Nasal shedding was significantly reduced and virus was cleared from the lung by day 5 postinfection following heterologous challenge of Ad5-HA-vaccinated pigs. However, the WIV-vaccinated pigs displayed vaccine-associated enhanced respiratory disease (VAERD) following heterologous challenge,characterized by enhanced macroscopic lung lesions. This study demonstrates that a single intranasal vaccination with an Ad5-HA construct can provide complete protection from homologous challenge and partial protection from heterologous challenge, as opposed to VAERD, which can occur with adjuvanted WIV vaccines.